Wilson-Jones angiosarcoma of the scalp associated with alopecia and chest edema: a case report - Galal El Enany; Noha Nagui; Hanan Nada; Marwa M Fawzy; Iman Sany; Suzan Shalaby; Omar El Ghanam (Wolters Kluwer Medknow Publications, 2022)
Wilson-Jones angiosarcoma is one of cutaneous angiosarcomas, which is a rare aggressive tumor of blood vessels of the skin. In this case report, we present a 72-year-old female who developed multiple episodes of facial edema of 2-year duration along with partial hair loss of the scalp. Investigations, including a skin biopsy, were diagnostic of scalp angiosarcoma.